Reduced metal nanocatalysts for selective electrochemical hydrogenation of biomass-derived 5-(hydroxymethyl)furfural to 2,5-bis(hydroxymethyl)furan in ambient conditions - Muchharla, Baleeswaraiah; Dikshit, Moumita; Pokharel, Ujjwal; Garimella, Ravindranath; Adedeji, Adetayo; Kumar, Kapil; Cao, Wei; Elsayed-Ali, Hani; Sadasivuni, Kishor Kumar; Al-Dhabi, Naif Abdullah; Kumar, Sandeep; Kumar, Bijandra (Frontiers in Chemistry, 2023)
Selective electrochemical hydrogenation (ECH) of biomass-derived unsaturated organic molecules has enormous potential for sustainable chemical production. However, an efficient catalyst is essential to perform an ECH reaction consisting of superior product selectivity and a higher conversion rate. Here, we examined the ECH performance of reduced metal nanostructures, i.e., reduced Ag (rAg) and reduced copper (rCu) prepared via electrochemical or thermal oxidation and electrochemical reduction process, respectively. Surface morphological analysis suggests the formation of nanocoral and entangled nanowire structure formation for rAg and rCu catalysts. rCu exhibits a slight enhancement in ECH reaction performance in comparison to the pristine Cu. However, the rAg exhibits more than two times higher ECH performance without compromising the selectivity for 5-(HydroxyMethyl) Furfural (HMF) to 2,5-bis(HydroxyMethyl)-Furan (BHMF) formation in comparison to the Ag film. Moreover, a similar ECH current density was recorded at a reduced working potential of 220 mV for rAg. This high performance of rAg is attributed to the formation of new catalytically active sites during the Ag oxidation and reduction processes. This study demonstrates that rAg can potentially be used for the ECH process with minimum energy consumption and a higher production rate.